Pengaruh Kualitas Pelayanan Dan Kompetensi Sumber Daya Manusia Terhadap Kinerja Pegawai Pada Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kabupaten Pesawaran - Rusanti, Tri; Ariswandy, David (Jurnal Multidisiplin Dehasen (MUDE), 2025)
The aim of this research is to analyze the influence of service quality and human resource competency partially and simultaneously toward employee performance. The hypothesis in this research is that there is a partial and simultaneous influence of service quality and human resource competency toward employee performance. This research was conducted at the Pesawaran Regency Investment and One-Stop Integrated Service. The type of research used is quantitative. The respondents in this study were 35 employees. The data collection techniques used were observation, documentation and questionnaires. The analytical tool used is multiple linear regression with hypothesis testing using the t test and f test. The research results show that there is an influence of service quality toward employee performance, as evidenced by tcount 9.888 > ttable 1.692. There is an influence of human resource competency toward employee performance, proven by tcount 9,815. > ttable 1.692. There is an influence of service quality and human resource competency together toward employee performance as evidenced by the Fcount value of 69.25 > Ftable 3.25. The contribution of service quality and human resource competency to employee performance is 81.2% and the remainder is influenced by other factors not analyzed in this research.